Improvement in Arabic Language Skills Through Implementation of Classroom Assessment (PBD) at Lower Secondary School Level - Satar, Hafilah Abd; Yusoff , Nik Mohd Rahimi Nik; Hamzah, Mohd Isa (International Journal of Psychosocial Rehabilitation, 2020)
Classroom assessment (PBD) is a continual process of evaluation in teaching to intensify student’s mastery and teachers’ teaching. This research attempted to explore the four forms of Arabic language advancement following the implementation of PBD in the classroom. The design of this qualitative research was a case study. The data were collected through extensive interviews of seven Arabic language teacher participants who were also appointed as the head coaches (JU) of PBD in five states in Malaysia. Interviewees were selected for purposive sampling on the premise that the study participants were proficient in Arabic PBD information. Subsequent study data were analysed with the aid of Nvivo 12 software. The findings confirmed that the results of the planned implementation of the Arabic language could change the objectives of the four Arabic language skills. These involved the four Arabic language skills emphasised throughout the course of instruction, students’ skills assigned according to their competency level, objective improvement of Arabic language skills, early detection of their competency level, vocabulary improvement, sentence development ability and implicit syntax exposure. Substantially, the findings demonstrated that the execution of PBD could enhance the teaching and learning process of the Arabic language, particularly in terms of enhancing four Arabic language skills among lower secondary school students.